CYBER RELIGION: Implementasi Keberagamaan dan Respons Generasi Milenial - Kuswana, Dadang; Syah, Yoshy Hendra Hardiyan; Aripudin, Acep (Al-Adyan: Journal of Religious Studies, 2023)
This article discusses the practice of religion in cyberspace and the response of the millennial generation to the social media account @Bimbingan_Islam, as a form of practice of Cyber Religion. The account discusses various study themes, including the theme of patience, life advice, istiqomah in worship, the glory of dhikr, the glory of praying, and others. The purpose of this study is First, to find out how the world of Cyber Religion is on the YouTube, Instagram, and Facebook platforms @Bimbingan_Islam. Second, to find out how the millennial generation responds in the comments column to posts on religious studies on the Instagram platform account @Bimbingan_Islam. This article uses qualitative research methods using data collection techniques (Literature Review) with a non-participatory virtual ethnographic approach and analysis techniques using Lasswell's communication theory. The limitations of the millennial generation referred to in this article are in the age range of 18 to 34 years. What's interesting in this article is that it displays technological developments, illustrations of information dissemination, the level of popularity of social media, and the spread of religious studies in cyberspace, making it a powerful attraction for the millennial generation to continue to deepen, upgrade, and hone their insights about religion, namely on account @ Bimbingan_Islam, then this article finds a case on the social media account, namely there is a sentence that is inappropriate to be presented to the public by using strong language in broadcasting religious studies through social media. Artikel ini membahas tentang praktik agama di dunia maya dan respon generasi milenial pada akun media sosial @Bimbingan_Islam, yaitu Cyber Religion. Akun tersebut membahas berbagai macam tema kajian, seperti kesabaran, nasehat hidup, istiqomah dalam beribadah, kemuliaan zikir, salawat, dan lain-lain. Tujuan penelitian ini adalah mengungkap bagaimana dunia Cyber Religion dalam platform YouTube, Instagram, dan Facebook pada akun @Bimbingan_Islam. Selanjutnya mengetahui bagaimana respon generasi milenial dalam kolom komentar terhadap postingan kajian agama pada plaform Instagram akun @Bimbingan_Islam. Metode penelitian kualitatif digunakan melalui pengumpulan data studi pustaka (Literature Review) dengan pendekatan etnografi virtual yang bersifat non-partisipasi. Kemudian dianalisis menggunakan teori komunikasi Laswell. Artikel ini memperlihatkan perkembangan teknologi, ilustrasi penyebaran informasi, tingkat popularitas media sosial, dan penyebaran kajian agama. Ini membuat daya tarik yang dahsyat bagi generasi milenial untuk senantiasa terus memperdalam, mengupgrade, dan mengasah wawasan tentang agama. Namun dalam akun @Bimbingan_Islam, ditemukan suatu kasus, yaitu terdapat suatu kalimat yang tidak pantas untuk disajikan kepada khalayak publik dengan menggunakan bahasa yang kasar dalam menyiarkan kajian agama melalui media sosial.